Nuclear Accumulation of HSP70 in Mouse Skeletal Muscles in Response to Heat Stress, Aging, and Unloading With or Without Reloading - Apostolopoulos, Antonios; Nakamura, Ayane; Yokoyama, Shingo; Aoshima, Megumi; Fujimoto, Risa; Nakamura, Kodai; Ito, Rika; Goto, Katsumasa (Frontiers in Genetics, 2018)
The purpose of this study was to investigate the nuclear accumulation of heat shock protein 70 (HSP70), a molecular chaperonin in mouse skeletal muscle in response to aging, heat stress, and hindlimb unloading with or without reloading. Profiles of HSP70-specific nuclear transporter Hikeshi in skeletal muscles were also evaluated. Heat stress-associated nuclear accumulation of HSP70 was observed in slow soleus (SOL) and fast plantaris (PLA) muscles of young (10-week old) mice. Nuclear accumulation level of HSP70 in slow medial gastrocnemius (MGAS) of aged (100-week old) mice was significantly higher than that of young (10-week old) mice (p<0.05). Reloading following 2-week hindlimb unloading caused accumulation of HSP70 in myonuclei in MGAS and PLA of young mice (p<0.05). However, reloading-associated nuclear accumulation of HSP70 was not observed in both types of muscles of aged mice. On the other hand, 2-week hindlimb unloading had no impact on the nuclear accumulation of HSP70 in both muscles of young and aged mice. Nuclear expression level of Hikeshi in both MGAS and PLA in mice was suppressed by aging. No significant changes in the nuclear Hikeshi in both muscles was induced by unloading with or without reloading. Results of this study indicate that the nuclear accumulation of HSP70 might show a protective response against cellular stresses in skeletal muscle, and that the protective response may be suppressed by aging. Protective response to aging might be depend on muscle fiber types.